Production of digital content in music teacher education: a study about podcast’s possibilities - Garcia, Marcos da Rosa; Marques, Gutenberg Lima; Barros, Matheus; Beltrame, Juciane Araldi (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação Musical, 2021)
This short paper presents an ongoing research that intertwines the theme of educational digital content production for the internet, specifically the audio podcast format, with the pedagogical practices developed in the context of music teacher education and emergency remote teaching. We aim at analyzing the experience of producing digital pedagogical-musical content in the podcast format by students of two Music Education Degree courses. The study uses a qualitative approach and the methodological strategy is based on concepts of action-research. The research is being developed by Technologies and Music Education Research Group (Tedum-UFPB) and by a team of professors from two federal higher education institutions. Data collection will be carried out through the development of field diaries by the research team and through conversation roundtables with the participant students, besides the entire process of documentation, registration and analysis of the phases that make up the action-research cycle. The research presented here can contribute to the processes of creation and conception of audio format content, seeking methodologies that are specific to the musical field, enhancing collective spaces for creation, valuing different authorships and encouraging pedagogical and musical diversity.